Identidade pantaneira: uma reflexão sobre a expressão artística do povo pantaneiro - Anitablian, Laura de Barros Marinho (2024)
This research aimed to identify significant symbols in the artistic production of the Pantanal people, focusing on visual arts, music and literature. We identified and analyzed five symbols: the mother-fig tree, the cowboy (peão boiadeiro), the bugre, the lonely man and the waters. From these symbols, one can better understand the deep relationship between local culture and the natural environment. The role of nature as a mother, who cares and is cared for, intuition as a way of connecting to nature, a sporting spirit to face difficulties, the loneliness of life in infinite spaces, the notion of totality based on life cycles and death. By analyzing these symbols and reflecting on Pantaneiro's relationship with them, we hope to contribute effectively to a broader understanding of the soul and culture of the Pantaneiro people